Social protection as an invisible component of the corporate social responsibility of construction enterprises - Loktionova, Yana (Ways to Improve Construction Efficiency, 2024)
Social protection is a key element of corporate social responsibility (CSR) of construction enterprises, as it determines the level of well-being of employees, their motivation and productivity, and also affects the overall reputation of the company. The article examines the importance of social protection as an integral component of CSR in the construction industry, identifies the main directions of its implementation and analyzes the factors that contribute to the effective implementation of social guarantees at enterprises. The construction sector is characterized by a high level of risk for employees, therefore, ensuring safe working conditions is of particular importance. The implementation of labor protection standards, regular training of personnel and the provision of necessary protective equipment are important aspects of the social responsibility of companies. In addition, social protection includes guaranteeing stable wages, medical insurance, pension provision, as well as the implementation of social support programs for employees and their families. An effective social policy of a construction enterprise also involves creating conditions for the professional development of employees. An important aspect is improving the skills of personnel, providing opportunities for career growth and training in modern technologies in construction. This not only increases the level of staff satisfaction, but also has a positive effect on the quality of construction work and the competitiveness of the company. In addition to internal social policy, construction companies actively interact with local communities. Investing in social infrastructure, supporting housing programs, participating in charitable initiatives and developing partnerships with local governments contribute to increasing the level of trust in the company and its sustainable development. Thus, social protection in construction companies is not only a moral obligation, but also a strategic tool for forming a positive image, increasing employee productivity and ensuring long-term economic stability. The implementation of comprehensive social protection measures allows construction companies not only to fulfill their obligations to employees, but also to contribute to the development of society as a whole.